High Road Leadership: bringing people together in a World that divides - Maxwell, John. (New York Forefront Books, 2024)
The world$1 (Bs most influential leadership expert, John C. Maxwell, tackles the problem of our divided world in his latest book High Road Leadership. (3z(BEverything rises and falls on leadership,(3y (Bsays Maxwell. (3z(BToday it is causing people to fall$1 (Binto disputes, frustration, anger, and despair. His solution is to expose the problems of taking the low and middle roads when interacting with others and teach people how to instead take the high road. Leaders who practice high road leadership value all people, do the right things for the right reasons, take accountability for their actions, and place people above their own agenda. In his trademark communication style, Maxwell teaches the principles and practices of high-road leadership that can increase anyone$1 (Bs influence and help them make their world a better place.s
Keywords: Leadership